2011
DOI: 10.1016/j.diagmicrobio.2010.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular characterization of recent and archived Erysipelothrix spp. isolated from Brazilian swine

Abstract: One hundred fifty-one Erysipelothrix spp. isolates from Brazilian swine were characterized by serotyping, determination of antimicrobial susceptibility, amplified fragment length polymorphism (AFLP), and pulsed-field gel electrophoresis (PFGE). Among all isolates, 139 were classified in 18 different serotypes and serotype 2b was the most frequent. The susceptibility profiles of the isolates were very similar among each other, which did not permit subtyping Erysipelothrix spp. isolates by the antimicrobial susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
5
10
0
4
Order By: Relevance
“…All five colonies presented identical susceptibility profiles, and their sensitivity as well as resistance to the drugs tested were compliant with other reports (Fidalgo et al 2002;Coutinho et al 2011).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…All five colonies presented identical susceptibility profiles, and their sensitivity as well as resistance to the drugs tested were compliant with other reports (Fidalgo et al 2002;Coutinho et al 2011).…”
Section: Discussionsupporting
confidence: 80%
“…As in other studies (Eriksson et al 2009;Coutinho et al 2011), the present investigation showed that the PFGE technique is a suitable method for E. rhusiopathiae genotyping. In the present study, an interesting and unpublished result was observed, three different genotypes were found among the five colonies collected from the same clinical specimen, ratifying the high discriminatory power of the PFGE technique and demonstrating, for the first time, the occurrence of infection by E. rhusiopathiae with different genotypes.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, this is not absolute and certain serovars can be associated with more than one species (5,29). Serotyping studies have indicated that, with some geographic differences, serovars 1a, 1b, and 2 are most widely distributed in pigs and likely of greatest importance overall (24,(29)(30)(31)(32)(33)(34)(35)(36) (Figure 2). Serotyping is not performed routinely, and serovars are not species specific or phylogenetically informative (37).…”
Section: Introductionmentioning
confidence: 99%
“…Live attenuated vaccines and bacterins have long been used successfully to control swine erysipelas (4). However, the high incidence of swine erysipelas is still a concern for the pork industry worldwide (5)(6)(7)(8); therefore, the development of new and more effective vaccines is desired.…”
mentioning
confidence: 99%